Influencer Strategies in Promoting Yogyakarta Tourism: AI Analysis of Engagement and Digital Narrativesl - Septia Winduwati; Resfirahma Resfirahma; Manda Aulia Az Zahra (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
Social media has become crucial in tourism destination marketing, with influencers playing a significant role in shaping tourist perceptions and decisions. In Yogyakarta, promotions by influencers on platforms like Instagram and TikTok have increased the popularity of various tourist attractions. This phenomenon demonstrates a shift in tourism information search patterns, which are increasingly reliant on digital recommendations and visual experiences shared online. However, academic studies on the effectiveness of influencer communication strategies and audience engagement, particularly those related to the use of Artificial Intelligence (AI), are still limited. This study analyzes influencers' digital communication strategies in promoting Yogyakarta tourism and explores the potential of AI in analyzing digital engagement and narratives. Using a mixed-methods approach with qualitative analysis of in-depth interviews, the study uncovers influencer strategies that focus on aesthetic content, authentic narratives, audience interaction, and trend adaptation. Furthermore, the study highlights the importance of message consistency and influencer credibility in building audience trust. AI is beginning to be utilized for creative efficiency (caption writing, visual editing) and has significant potential for analyzing audience engagement and sentiment. The findings indicate that digital influencer promotions have a positive impact on tourist decisions and support local tourism, although challenges of originality and content competition remain. Theoretically, this research contributes to the study of digital communication and tourism marketing, while practically, the results can be utilized by influencers, the tourism industry, and policy makers in designing data-based marketing strategies.